A CHARACTERISTIC OF MORPHOLOGY, COLONY AND BIOCHEMISTRY OF BACTERIA THAT ISOLATED FROM SEDIMENTS OF MOSQUITO BREEDING LAGOON - Maruni wiwin Diarti; Rohmi rohmi; Yuri Syaffitri Kinanti Achmad; Yunan Jiwintarum (poltekkes kemenkes mataram, 2017)
The lagoon is a form of semi-enclosed bay which is one type of an estuary. In lagoon water there is a meeting and mixing of freshwater and seawater thus it causes free relationship between the sea and the source of freshwater. The effect of tides that mixed with freshwater will cause a change of the aquatic character instantly. It will certainly affect the diversity of organism species, including bacteria. Some types of bacteria, one of them is Bacillus, it is basically soil bacteria, but commonly found in fresh and brackish waters. The purpose of this study was to determine the characteristics of morphology, colonies and biochemistry of bacteria that isolated from sediments of mosquito breeding lagoon in the coast of Medana village, Tanjung district, North Lombok regency. This research was descriptive observational, used non random purposive sampling with 15 samples. Data collected in the form of types of bacteria found in 15 points from sediments of mosquito breeding lagoon. The data analysis used descriptive analysis. The results of 15 points of lagoon sediments that isolated, from 15 bacteria colonies that was identified as morphological, colonies and biochemical characteristics found three types of bacteria: Aeramonas schubertii, Bacillus subtilis, and Enterbacter agglomerans. The conclusion is the sediments of mosquito breeding lagoon in the coast of Medana Village, Tanjung district, North Lombok regency is obtained the bacteria, for instace: Aeramonas schubertii, Bacillus subtilis, and Enterobacter agglomerans.